New records of Namibian Bombyliidae (Diptera), with notes on some genera and descriptions of new species - Greathead, David J. (Zootaxa, 2006)
Bombyliidae in the Namibian National Insect Collection and the Albany Museum, Grahamstown, South Africa were identified. This material included six genera and 54 species not previously recorded from Namibia. Among these species three were found to be new and are described: viz., Heterotropus diamantis sp. nov., Hyperusia longirostris sp. nov., Exoprosopa gracilis sp. nov. In addition a new species  is proposed, Doliogethes decipiens sp. nov. for the species misidentified as Doliogethes tripunctatus (Macquart) by previous authors.  Six new junior synonyms are proposed: Anastoechus eurystephus Hesse (= A. macrophthalmus Bezzi), syn. nov.; Anastoechus leuchocroicus Hesse (=A. vatipecten Bezzi), syn. nov.; Doliogethes consobrinus Hesse and D. meridionalis Hesse (= D. aridicolus Hesse), syn. nov.; Systoechus bechuanus Hesse (= S. robustus Bezzi), syn. nov.; Heteralonia (Acrodisca) nephoneura (Hesse) (= H. (A.) katonae (Bezzi)). A supplement to the checklist of Bombyliidae of Namibia including full label data is provided.